2015
DOI: 10.1007/s00402-015-2199-5
|View full text |Cite
|
Sign up to set email alerts
|

Static progressive versus dynamic splinting for posttraumatic elbow stiffness: a systematic review of 232 patients

Abstract: Both dynamic orthoses and static progressive splinting show good results for the treatment of elbow stiffness, regardless of etiology. The choice for one treatment over the other is based on the preference of the surgeon and patient. We recommend to continue nonoperative treatment with dynamic or static bracing for 12 months or until patients stop making progression in range of elbow motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Firstly, the overall methodological quality of the studies was fair and included only three RCTs, while it furthermore consisted of observational studies. Although previous studies have also used this methodology of combining both RCT's and observational trials [50,51], it is important to note that the risk of bias is substantially larger in observational studies. Secondly, the heterogeneity of the used interventions between included studies was high.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the overall methodological quality of the studies was fair and included only three RCTs, while it furthermore consisted of observational studies. Although previous studies have also used this methodology of combining both RCT's and observational trials [50,51], it is important to note that the risk of bias is substantially larger in observational studies. Secondly, the heterogeneity of the used interventions between included studies was high.…”
Section: Discussionmentioning
confidence: 99%
“…przedoperacyjnie, zaburzeniach prawidło-wych stosunków anatomicznych. Samo wprowadzenie kinezyterapii wydawało się konieczne ze wzglę-du na zagrożenie dysfunkcją stawu łokciowego, wynikającą z nakładającego się okresu unieruchomienia po pierwszym i drugim zabiegu operacyjnym [23,24].…”
Section: Discussionunclassified
“…pre-operative, abnormal anatomy of the region. Kinesiotherapy itself did seem necessary due to the risk of elbow dysfunction caused by accumulating periods of immobilisation after the first and second surgery [23,24].…”
Section: Discussionmentioning
confidence: 99%
“… 21 Within the early phase, splinting, either static or dynamic, has proven helpful. 22 - 24 Schwartz, 25 in a literature review, and Müller et al, 26 in a recent meta-analysis, both found support for the use of static-progressive splinting when used in the early phase of post-traumatic and post-operative stiffness. Non-operative treatment also usually includes physiotherapy, guided range of movement exercises and passive mobilizations.…”
Section: Conservative Treatmentmentioning
confidence: 96%